Analysis of Policy Implementation for Peatland Ecosystem Degradation Control on Community Land in the Ex-PLG Area of Central Kalimantan Province - Irwani, Sabitah; Hariyadi; Kartodihardjo, Hariadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Degradation of peatland ecosystem on community land is controlled by the article 32 A paragraph (3) of Government Regulation Number 57 of 2016 concerning Amendments to Government Regulation Number 71 of 2014 concerning Protection and Management of Peatland Ecosystems which provide explicit direction that the restoration of peatland ecosystem forest and functions owned by the community or indigenous peoples is their responsibility. To assist the community to have countermeasures actions for peatland ecosystem degradation on the community land, the government has implemented the Peatland Self-supporting Villages (Desa Mandiri Peduli Gambut) program since 2016 in several provinces including Central Kalimantan Province. This study aims to: (1) analyze the current policy for controlling degradation to the peatland ecosystem if it applied to community land, and (2) Analyze the implementation of the policy for controlling degradation to the peatland ecosystem through the implementation of the Peatland Self-supporting Villages in the ex PLG area of Central Kalimantan Province by assessing the sustainability and implementation strategy of the program. The results of the study are: (1) The peatland ecosystem destruction control policy that has been applied to the licensed land can be applied to community land as long as they has sufficient capacity (2) the sustainability assessment of the implementation of the Peatland Self-supporting Villages program in the ex-PLG Area of ​​Central Kalimantan Province is included in the “moderate” category with an index value of 68.54, while the main strategy for proper implementation is by conducting exposure meetings of the Community Work Plan (Rencana Kerja Masyarakat, RKM) document to the relevant agencies and collaborating through programs that are in accordance with their duties.